Elucidation of the molecular mechanism and the efficacy in vivo of a novel 1, 4‐benzoquinone that inhibits 5‐lipoxygenase. (May 2014) - Schaible, A M; Filosa, R; Temml, V; Krauth, V; Matteis, M; Peduto, A; Bruno, F; Luderer, S; Roviezzo, F; Di Mola, A; de, M; D'Agostino, B; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose 1, 4‐Benzoquinones are well‐known inhibitors of 5‐lipoxygenase (5‐LOX, the key enzyme in leukotriene biosynthesis), but the molecular mechanisms of 5‐LOX inhibition are not completely understood. Here we investigated the molecular mode of action and the pharmacological profile of the novel 1, 4‐benzoquinone derivative 3‐((decahydronaphthalen‐6‐yl)methyl)‐2, 5‐dihydroxycyclohexa‐2, 5‐diene‐1, 4‐dione (RF‐Id) in vitro and its effectiveness in vivo. Experimental Approach Mechanistic investigations in cell‐free assays using 5‐LOX and other enzymes associated with eicosanoid biosynthesis were conducted, along with cell‐based studies in human leukocytes and whole blood. Molecular docking of RF‐Id into the 5‐LOX structure was performed to illustrate molecular interference with 5‐LOX. The effectiveness of RF‐Id in vivo was also evaluated in two murine models of inflammation. Key Results RF‐Id consistently suppressed 5‐LOX product synthesis in human leukocytes and human whole blood. RF‐Id also blocked COX‐2 activity but did not significantly inhibit COX‐1, microsomal PGE2 synthase‐1, cytosolic PLA2 or 12‐ and 15‐LOX. Although RF‐Id lacked radical scavenging activity, reducing conditions facilitated its inhibitory effect on 5‐LOX whereas cell stress impaired its efficacy. The reduced hydroquinone form of RF‐Id (RED‐RF‐Id) was a more potent inhibitor of 5‐LOX as it had more bidirectional hydrogen bonds within the 5‐LOX substrate binding site. Finally, RF‐Id had marked anti‐inflammatory effects in mice in vivo. Conclusions and Implications RF‐Id represents a novel anti‐inflammatory 1, 4‐benzoquinone that potently suppresses LT biosynthesis by direct inhibition of 5‐LOX with effectiveness in vivo. Mechanistically, RF‐Id inhibits 5‐LOX in a non‐redox manner by forming discrete molecular interactions within the active site of 5‐LOX.